POTENSI EKSTRAK METANOL DAUN KAPUR (Harmsiopanax aculeatus, Harms) SEBAGAI OBAT ANTIMALARIA - Wijaya, Jefry; Salenussa, Jusuf; Marantika, Jacky (Program Kreativitas Mahasiswa - Penelitian, 2013)
Kapur plant (Harmsiopanax aculeatus Harms) is traditionally used by Mollucans to treat malaria disease. Squeezed of young leaves which is dropped on the eye of sufferer is the way of its treatment. This research is aimed to assay haem polymerization inhibition activity, cytotoxic activity toward vero cells and to analysis chemical secondary metabolit of compound content on methanol extract of the old kapur leaves. Dried powder of kapur leaves (1 kg) is extracted by maceration technique using methanol solvent obtained 95,85g (9,59%) of methanol extract. Those extract which assayed haem polymerization inhibition on activity by Bassilico et al. (1998) method is shown IC50 values of 9410,93 µg/mL. Cytotoxic test toward vero cells using MTT assay, Kasugai et al. (1983) is shown that IC50 values is 9402,81 µg/mL. Phytochemical analysis by spray and visible reagent shown of flavanoids, phenolic, saponin an antraquinones compound. Keyword: Harmsiopanax acuelatus Harms, haem polymerization inhibition activity, cytotoxic activity, vero cell, phytochemical.